Development of mobile robot controlled by android phone via Bluetooth - Wan Idris Najaran, Wan Nur 'Amirah (2015)
This robot was designed so that it can be controlled by an android phone instead of using the usual controller, which would be the PS2 controller. The android phone acts as a remote control to operate the movements of the robot. The robot is controlled wirelessly using the Bluetooth feature which is present in all android smart phones. A Bluetooth module is mounted on the robot to allow wireless communication between both the android phone and the robot. An open sourced application called Blue Control is downloaded into the android smart phone to enable the communication between both the android phone and the robot. This application acts as an interface between both devices. PIC microcontroller is used as a controlling device for this whole system. It is programmed to implement the movement algorithm of this robot.